ANALISIS DEBIT AIR DI SUB DAS NAHIYAH DAS ASAM-ASAM KABUPATEN TANAH LAUT - Reznandi Wiharto Fitrian Sulaxono; Eko Rini Indrayatie; Syarifuddin Kadir (Jurnal Sylva Scienteae, 2020)
The purpose of this study is to determine the value of the Water Discharge in the Nahiyah Asam-Asam watershed sub-watershed. Measure of water discharge is carried out using two methods. The first method uses a current meter, while the second method uses a float and is accompanied by a measurement of Water Level (WL) using a Piscal tool. There are two data taken namely primary data and secondary data. The research was conducted from January 2019 to April 2019. Based on the result obtained, it is known that the upstream water discharge with an average water flow of 2,38 m3/second. In the middle water flow with an average water flow of 4,27 m3/second. In the downstream water discharge with an average water discharge of 8,16 m3/second.Keyword: water discharge; upstream; middle; downstream